The Jesuit Encounters with Islam in the Asia-Pacific - Coello de la Rosa, Alexandre (Brill, 2023)
This book explores the strategies adopted by the Jesuit missions under the Portuguese and Spanish patronage before Islamic powers such as the Mughal Empire in South Asia and the expansion of Islam in the Southeast Asian peripheries. Based on a comparative perspective, this book examines the interconnections between the Jesuit proselytizing activities and the imperial projects of the Iberian crowns in Asia, highlighting the role of the Jesuit missionaries operating in Asian Islamic settings as diplomatic and cultural mediators. It is aimed at researchers and students working on Jesuit missions in South Asia, the Portuguese and Spanish empires in Asia, early modern cross-cultural diplomacy, early modern travel accounts, and early modern ethnography.